Description of 3 cases of skin and soft tissue infections caused by Streptococcus pneumoniae Descripción de 3 casos de infecciones de piel y tejidos blandos por Streptococcus pneumoniae - Martínez, Mónica Elisabeth (2017)
The role of Streptococcus pneumoniae as a causative agent of skin and soft tissue infections (SSTI) is unusual and its clinical interpretation is difficult. We describe here three cases of SSTI due to S. pneumoniae in patients admitted to the Provincial Pediatric Hospital of Misiones, Argentina that were detected during 10 years of invasive disease (ID) surveillance documented in 2010, 2011 and 2015. These cases involved two girls aged 8 and 7 months old, and a two-year-old male child with diagnoses of gluteal abscess, preseptal cellulites and pyoderma respectively. All the patients were eutrophic and in good general condition on admission; one of them was seropositive for HIV. Antimicrobial susceptibility and serotypes were framed within the local epidemiology of invasive pneumococcal disease. Despite its low frequency, S. pneumoniae as an etiological agent of SSTI must be considered. Our findings revalue the role of the diagnostic laboratory and contribute to document the behavior of this pathogen.